Mossbauer Spectral Studies of Some Fe(III)-Ketoanil Complexes - Pathak, Vishal; Bharadwaj, K.K.; Agrawal, Anshu (Asian Journal of Chemistry, 2010)
Studies incorporated in this communication are related to the chemical aspects of high and low spin Fe(III) complexes involving some previously synthesized complexes of hexadentate heterocyclic ketoanil p-phenyldianil of 2-thiophenglyoxal (PDATG) along with different anionic ligands, which include the ascertainment of stereochemistries and nature of metal-ligand bonds in the complexes as indicated in our previous findings.